Biofilms in the Food Industry: Health Aspects and Control Methods - Galié, Serena; García-Gutiérrez, Coral; Miguélez, Elisa M.; Villar, Claudio J.; Lombó, Felipe (Frontiers in Microbiology, 2018)
Diverse microorganisms are able to grow on food matrixes and along food industry infrastructures. This growth may give rise to biofilms. This review summarizes, on the one hand, the current knowledge regarding the main bacterial species responsible for initial colonization, maturation and dispersal of food industry biofilms, as well as their associated health issues in dairy products, ready-to-eat foods and other food matrixes. These human pathogens include Bacillus cereus (which secretes toxins that can cause diarrhea and vomiting symptoms), Escherichia coli (which may include enterotoxigenic and even enterohemorrhagic strains), Listeria monocytogenes (a ubiquitous species in soil and water that can lead to abortion in pregnant women and other serious complications in children and the elderly), Salmonella enterica (which, when contaminating a food pipeline biofilm, may induce massive outbreaks and even death in children and elderly), and Staphylococcus aureus (known for its numerous enteric toxins). On the other hand, this review describes the currently available biofilm prevention and disruption methods in food factories, including steel surface modifications (such as nanoparticles with different metal oxides, nanocomposites, antimicrobial polymers, hydrogels or liposomes), cell-signaling inhibition strategies (such as lactic and citric acids), chemical treatments (such as ozone, quaternary ammonium compounds, NaOCl and other sanitizers), enzymatic disruption strategies (such as cellulases, proteases, glycosidases and DNAses), non-thermal plasma treatments, the use of bacteriophages (such as P100), bacteriocins (such us nisin), biosurfactants (such as lichenysin or surfactin) and plant essential oils (such as citral- or carvacrol-containing oils).